Grid compliance for gas turbine power generation - Yang, Shicong (2016)
Due to their low greenhouse gases emission, high efficiency and the availability of fuel gas, gas turbine powered generations have become one of most popular electricity generation systems. In this connection, a computer-based simulation model of gas turbine is most necessary when it comes to the study the dynamics of gas turbine system. For this purpose, the model proposed by Rowen is the most commonly used. However, it is not readily available in MATLAB software. This thesis presents the construction and validation of Rowen’s model under the Matlab/Simulink platform. Open-loop tests, closed-loop tests are conducted, and simulation results are presented and discussed. A three phase ground fault is simulated to observe the performance of a specific gas turbine, and the simulation results are compared with those obtained from field-tests. The two sets of results appear to agree amicably well.